REPRESENTASI AKTOR SOSIAL DALAM PEMBERITAAN JUDI ONLINE PADA LAMAN BERITA DETIK.COM : ANALISIS WACANA KRITIS BERBASIS KORPUS - Anggraini Putri Rahma Sivana; Sidiq Budiawan, Raden Yusuf; Arifin, Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reporting on online gambling is highly prevalent in Indonesia and extensively covered by online mass media. This study aims to describe the representation of social actors in online gambling coverage on Detik.com through corpus-based discourse analysis. The research employs a mixed-methods approach, combining both qualitative and quantitative methodologies. Data was collected using Octoparse software and analyzed using AntConc software. The findings reveal that Detik.com’s reporting deliberately emphasizes certain social actors and actions to construct the narrative. Roles such as perpetrators, victims, and the police are portrayed as central elements in the online gambling crime narrative, whereas the role of the government is depicted in a normative and administrative manner. Furthermore, the study finds that news coverage not only serves as an information source but also influences public opinion by obscuring power structures and economic interests behind online gambling promotions. These findings indicate that corpus-based discourse analysis effectively uncovers hidden agendas and biases in news texts, impacting public perception and attitudes.